Mekanisme Pendistribusian Tabung Gas Elpiji 3 Kg Bersubsidi Dalam Perspektif Ekonomi Islam - Fitri Fatimawati; Rika Fitriani (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The study’s findings are expected to serve as a reference for designing more targeted and effective economic empowerment programs for the poor. This study aims to examine the mechanism of distributing subsidized 3 kg LPG gas cylinders from the perspective of Islamic economics. The government subsidy for 3 kg LPG gas is intended to alleviate the burden on society, especially low-income groups. However, in practice, the distribution of 3 kg LPG often faces various challenges, such as subsidy misuse, uneven distribution, and price injustices. From the perspective of Islamic economics, principles of justice, balance, and efficiency must be upheld in every aspect of the distribution of goods and services, including subsidized energy. This research uses a descriptive-analytical approach to analyze the distribution policy of subsidized 3 kg LPG in the context of Islamic economic principles, such as social justice, the avoidance of riba (usury), and the provision of quality goods for all levels of society. The findings show that although the 3 kg LPG subsidy aims to improve the welfare of the poor, the current distribution system does not fully align with the principles of Islamic economics. It is recommended that the distribution system be more transparent, efficient, and prioritize justice, ensuring that subsidies are properly targeted and not misused by ineligible parties. This study contributes to providing insights for energy policies that are more just and in line with the values of Islamic economics.